Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 145274 by ArielVyny last updated on 03/Jul/21

∫_(∣z∣=1) ((f^− (z))/(z−a))dz

z∣=1f(z)zadz

Answered by Olaf_Thorendsen last updated on 03/Jul/21

f(a) = (1/(2πi))∮_γ ((f(z))/(z−a)) dz  Ω = ∫_(∣z∣=1) ((f^_ (z))/(z−a)) dz  Ω = 2πif^_ (a)

f(a)=12πiγf(z)zadzΩ=z∣=1f_(z)zadzΩ=2πif_(a)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com